Columbia or High School? : Understanding the Roles of Education in Development - Ramcharan, Rodney (IMF Working Papers; Working Paper ;, 2002)
No country has achieved sustained economic development without investment in education. Thus, education policy can play a vital role in facilitating development. But which types of schooling-secondary or tertiary-should public policy promote? This paper develops an analytical framework to address this question. It shows how the composition of human capital stock determines a country's development. Hence, promoting the "wrong" type of schooling can have little effect on development. In addition to identifying some characteristics of an optimal education policy, the paper helps in understanding why empirical studies have failed to find a significant relationship between schooling and growth.